A espacialidade da indústria em Goiás: a nova "marcha para o oeste" - o exemplo de Catalão - Lima, Valdivino Borges de (2015)
This work, entitled SPATIALITY INDUSTRY IN GOIÁS: the new march to the West - the example of Catalão, was meant to demonstrate the industry's spatiality in Goiás and its connection with the world. The historical reference occurred since 1990, when, motivated by productive capital reorganization with effects in space and labor, the State has developed several programs in the context of industrial decentralization in the country. The problem was formulated as follows: what are the causes, the effects and contradictions generated by the spatiality of industrialization in Goiás since the 1990s? In the theoretical sense we interpret the industry’s spatiality in Goiás that weaving up to primary and tertiary sectors through the modernization process, was able to increase the economic growth of Goiás, generating migratory flows and an intense process of urban concentration , however, it did not solve what is more socially urgent: the social inequality and employment. For the research, methodological work is based on the understanding of the industry as part of a universal process with differential expression in the region and place, for which bibliographical, documentary and statistics sources were raised and treated cartographically with further analysis.